Internationalization at Home: A Reflection on a Semester-Long Online Collaborative Project Between Canadian and Indian Students - Thiessen, Tiare; Abraham, Iwona; Abraham, Liza (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2023)
In today’s global community, internationalization offers students a crucial advantage by developing their intercultural competence and global citizenship skills. Recent research on Internationalization at Home (IaH) has shown that students can benefit from this approach even without travelling. There has been minimal research conducted on how internationalization affects students’ attitudes towards environmental sustainability, which is another critical theme in our interconnected world. This study evaluates an IaH initiative’s impact on students’ environmental beliefs and values from Alberta, Canada, and Kerala, India. As an IaH initiative, this project engaged students in online collaboration with students from a different world region. Participants worked collaboratively on four tasks and completed an individual reflection assignment. Student and faculty feedback shows that participants improved their knowledge of environmental issues and their commitment to environmental sustainability. Additionally, students also demonstrated stronger intercultural communication and global citizenship skills.